Prognostic Value of Measurable Th1 Immune Response in the Tumors and Lymph Nodes of Patients with Lymph Node Positive and Lymph Node Negative Breast Cancer. Issue 2 (16th December 2019) - Thakur, Archana; Schalk, Dana L.; Lin, Tayson; Calme, Griffin; Ung, Johnson; PatcharinPramoonjago, PatcharinPramoonjago; Tranchida, Paul; Bandyopadhyay, Sudeshna; Choi, Lydia; Lum, Lawrence G.
No abstract available